Cu-impregnated alumina/silica bed materials for Chemical Looping Reforming of biomass gasification gas. (15th September 2016) - Keller, Martin; Fung, Jason; Leion, Henrik; Mattisson, Tobias
Abstract: Raw gas derived from low-temperature biomass gasification usually contains condensable hydrocarbons referred to as "tars" as well as other hydrocarbons such as ethylene and other olefins. Reforming of these compounds via Chemical Looping Reforming has been recently proposed. In this work Cu supported on four different Al2 O3 /SiO2 -based porous support materials were investigated for reforming of ethylene. The investigated particles were manufactured by incipient wetness impregnation of the porous support with a copper nitrate solution followed by calcination, and then tested in a small-scale fluidized bed reactor at temperatures between 600 °C and 850 °C. The ethylene conversion was found to be strongly inhibited by the presence of aromatics in the gas. However, it was found that Cu supported on commercial PURALOX transition alumina catalyst exhibited superior properties, with high degrees of ethylene conversion achievable even in the presence of aromatic compounds. Under the experimental conditions in this work, up to 90% ethylene conversion was obtained at T  = 850 °C in the presence of high concentrations of benzene. For the other prepared materials, the ethylene conversion was drastically reduced when monoaromatic compounds were present in the feed.